Improving Pain Relief in Elder Patients (I‐PREP): An Emergency Department Education and Quality Intervention. Issue 12 (2nd November 2016) - Hogan, Teresita M.; Howell, Michael D.; Cursio, John F.; Wong, Alexandra; Dale, William
Abstract : Objectives: To assess the effectiveness of a novel combined education and quality improvement (QI) program for management of pain in older adults in the emergency department (ED). Design: Controlled pre/postintervention examination. Setting: An academic urban ED seeing 60, 000 adult visits annually. Participants: Individuals aged 65 and older experiencing moderate to severe pain. Intervention: Linked standardized education and continuous QI for multidisciplinary staff in an urban, academic ED from January 2012 to January 2014. Measurements: Pain intensity, percentage receiving and time to pain assessment and reassessment, percentage receiving and time to delivery of analgesic. Results: The percentage of participants with final pain score of 4 or less (out of 10) increased 47.5% (95% confidence interval (CI) = 41.8–53.2%). Median decrease in pain intensity improved significantly, from 0.0 to 5.0 points ( P < .001). Median final pain score decreased from 7.0 to 4.0 points ( P < .001). The percentage of participants with any pain improvement increased 43.7% (95% CI = 37.1–50.3%, P < .001). Pain reassessments increased significantly (from 51.9% to 82.5%, P < .001). The percentage receiving analgesics increased significantly (from 64.1% to 84.8%, P < .001). After the intervention, participants had 3.1 (95% CI = 2.1–4.4, P < .001) greater odds of receiving analgesics and 4.7 (95% CI = 3.5–6.5, P < .001) greater odds of documented pain reassessment. Conclusion: The I‐PREP intervention substantially improved pain management in older adults in the ED with moderate to severe musculoskeletal or abdominal pain. Significant reductions in pain intensity were achieved, the timing of pain assessments and reassessments was improved, and analgesics were delivered faster. Tightly linking education to targeted QI improved pain management of older adults in the ED.